Profile of Primary Students' Conceptual Change about Water Dissolving Various Substances - Rosita, Ita; Suhandi, Andi; Sopandi, Wahyu (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Prior observation of the research indicated that many misconceptions occured in the learning process in elementary school. Therefore this study aims to determine the change profile of students' conceptions of water dissolving various kinds of substances. The strategy used is the learning strategy Predict Observe Explain (POE) which consists of three stages, namely predicting, observing, and explaining. The research method used was the preexperimental method with the research design of one group pretest-posttest. The subjects in this study were fifth grade students in one of the elementary schools in Bandung Regency. Based on the data obtained from the pretest sheet, the prediction sheet and post-test sheet, it was found that there was a change in conception in students who had attended the study using the POE strategy. This can be seen from the reduced number of students with the category of answers to misconceptions significantly and the other side there is an increase in students with the category of understanding answers. For this reason, researchers provide recommendations to use the POE strategy as a solution to improve the existence of misconceptions